Determination of the potential to provide reactive power from distribution grids to the transmission grid using optimal power flow - Goergens, Philipp; Potratz, Fabian; Godde, Markus; Schnettler, Armin (2015 50th International Universities Power Engineering Conference (UPEC), 2015)
This paper addresses the subject of determining the potential of distribution grids to provide reactive power to the transmission grid. A method based on optimal power flow is developed in order to determine the reactive power potential Day-Ahead taking meteorological data into account that decisively affects the contribution of distributed energy resources. The developed method is validated by simulations on the basis of a realistic low voltage grid with load measurements and meteorological (forecast and measurements) data. It can be summarized that the forecast of the reactive power potential that can be provided is of low quality due to forecast errors when the inverter of the of distributed energy resources is operated according to guidelines. By exploiting the theoretical potential of PVs inverter to a greater extent the reactive power potential is rather high and the forecast errors are less significant. The method enables for an improved predictability for transmission system operators with respect to reactive power balancing in the future and the results give first indications about the reactive power potential from the distribution grid for the transmission grid.